Polymerizable compound, polymerizable composition, optical film, and display device
By designing the bonding structure between cyclohexane-1,4-diyl groups and groups, the solubility of polymerizable liquid crystal compounds is improved and the phase transition temperature is reduced. Combined with dichroic pigments, dissolution in the prior art is solved The problems of insufficient properties and high phase transition temperature have achieved a high-performance polarizing film.
Patent Information
- Application Number
- CN202380040646.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-17
- Filing Date
- 2023-03-08
- Publication Date
- 2024-12-27
AI Technical Summary
The conventional polymerizable liquid crystal compound has insufficient solubility in the solvent and high phase transition temperature, resulting in a decrease in the film-forming properties of the polarizing film and a decrease in the dichroism ratio.
A new polymerizable compound has been developed, with a structure bonded to the group through an ester or ether structure through a cyclohexane-1,4-diyl group, which improves solubility in the solvent and reduces the phase transition temperature, and binds to A polymerizable composition formed by dichroic pigment.
The film-forming and dichroism ratio of the polarizing film under low temperature conditions is achieved, and the performance of the light absorption anisotropic film is enhanced.
Smart Images

Figure BDA0005135250190000021 
Figure BDA0005135250190000031 
Figure BDA0005135250190000061
Abstract
Description
Technical Field
[0001] The present invention relates to a polymerizable compound, a polymerizable composition comprising the polymerizable compound, an optical film comprising a polymer of the polymerizable compound or a cured product of the polymerizable composition, and a display device comprising the optical film. Background Art
[0002] In the past, in flat panel display devices (FPD), polarizing plates were used by being attached to image display elements such as liquid crystal cells and organic EL display elements. In recent years, along with the demand for thinning of flat panel display devices, in order to achieve thinning of polarizing plates and polarizing films as one of their components, for example, dichroic guest-host polarizers formed of a composition containing a polymerizable liquid crystal compound and a dichroic pigment as described in Patent Document 1 are used.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2007-510946 Summary of the invention
[0006] Problems to be solved by the invention
[0007] An optical film comprising a light absorption anisotropic film formed by a guest-host polarizer is usually made by the following process, that is, a composition comprising a solvent, a polymerizable liquid crystal compound and a dichroic pigment is applied to a film such as a substrate film to form a coating film, and the coating film is heated and dried to make the polymerizable liquid crystal compound phase transition to a liquid crystal state. In the past, there were many cases where the solubility in the solvent was insufficient due to its molecular structure, and the phase transition temperature to the liquid crystal phase was high. In the case of low solubility of the polymerizable liquid crystal compound, it is sometimes precipitated in the coating liquid or crystallized and precipitated. In addition, when the phase transition temperature of the polymerizable liquid crystal compound is high, it is necessary to heat to a temperature higher than the phase transition temperature of the polymerizable liquid crystal compound to make it phase transition when the light absorption anisotropic film is formed. The precipitation, precipitation, and heating at high temperature of such a polymerizable liquid crystal compound during the formation of the light absorption anisotropic film may become the cause of not only reducing the film-making property, but also reducing the dichroic ratio of the obtained light absorption anisotropic film.
[0008] An object of the present invention is to provide a polymerizable compound having excellent solubility in a solvent and a low phase transition temperature.
[0009] Means for solving problems
[0010] The inventors of the present application have conducted intensive studies to solve the above-mentioned problems and have completed the present invention. That is, the present invention provides the following preferred embodiments.
[0011] [1] A polymerizable compound represented by the following formula (1).
[0012] [Chemical formula 1]
[0013]
[0014] [In formula (1),
[0015] X1 and X2 are each independently a 1,4-phenylene group which may have a substituent or a cyclohexane-1,4-diyl group which may have a substituent (wherein at least one of X1 and X2 is a 1,4-phenylene group which may have a substituent), and the -CH 2 - can be replaced by -O-, -S- or -NR-, R represents an alkyl group with 1 to 6 carbon atoms or a phenyl group,
[0016] Y1 represents -CH 2 CH 2 -、-CH 2 O-, -COO-, -OCO-, -OCOO-, single bond, -N=N-, -CR a =CR b -, -C≡C- or -CR a =N-,R a and R b each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms,
[0017] U1 and U2 independently represent a hydrogen atom or a polymerizable group (wherein at least one of U1 and U2 is a polymerizable group),
[0018] W1 represents a single bond, -O-, -S-, -COO-, -OCO- or -OCOO-,
[0019] V1 and V2 are each independently an alkanediyl group having 1 to 20 carbon atoms which may have a substituent, wherein -CH 2 - may be replaced by -O-, -S-, -NH-, -COO-, -OCO- or -OCOO-.]
[0020] [2] The polymerizable compound according to [1] above, which exhibits a smectic liquid crystal phase.
[0021] [3] The polymerizable compound described in [1] or [2] above, wherein Y1 in formula (1) is a divalent group represented by -COO- or -OCO-, and W1 is a divalent group represented by -O-, -COO- or -OCO-.
[0022] [4] The polymerizable compound according to any one of [1] to [3] above, wherein U1 and U2 in formula (1) are acryloyloxy groups.
[0023] [5] A polymerizable composition comprising a dichroic dye and the polymerizable compound according to any one of [1] to [4] above.
[0024] [6] The polymerizable composition according to [5] above, further comprising a solvent.
[0025] [7] An optical film comprising a polymer of the polymerizable compound described in any one of [1] to [4] above, or a cured product of the polymerizable composition described in [5] or [6] above.
[0026] [8] The optical film according to [7] above, wherein the dichroic ratio is 20 or more.
[0027] [9] A display device comprising the optical film described in [8] above.
[0028] Effects of the Invention
[0029] According to the present invention, a polymerizable compound having excellent solubility in a solvent and a low phase transition temperature can be provided. DETAILED DESCRIPTION
[0030] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made within the scope that does not impair the gist of the present invention.
[0031] <Polymerizable compounds>
[0032] The polymerizable compound of the present invention is a compound represented by formula (1) (hereinafter also referred to as “polymerizable compound (1)”):
[0033] [Chemical formula 2]
[0034]
[0035] In the formula (1), X1 and X2 each independently represent a 1,4-phenylene group which may have a substituent or a cyclohexane-1,4-diyl group which may have a substituent.
[0036] Here, at least one of X1 and X2 is 1,4-phenylene which may have a substituent. -CH 2 - may be replaced by -O-, -S- or -NR-, and R represents an alkyl group having 1 to 6 carbon atoms or a phenyl group.
[0037] As the substituent that the 1,4-phenylene group which may have a substituent or the cyclohexane-1,4-diyl group which may have a substituent, there can be mentioned a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the hydrogen atom contained in the 1,4-phenylene group or the cyclohexane-1,4-diyl group may be substituted by any of the aforementioned groups. X1 and X2 in formula (1) are preferably unsubstituted 1,4-phenylene group or unsubstituted cyclohexane-1,4-diyl group. The cyclohexane-1,4-diyl group may be a cis isomer or a trans isomer.
[0038] In formula (1), Y1 represents -CH 2 CH 2 -、-CH 2 O-, -COO-, -OCO-, -OCOO-, single bond, -N=N-, -CR a =CR b -, -C≡C- or -CR a =N-,R a and R b Y independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1 More preferably -CH 2 CH 2 -、-COO-、-OCO-、-CH 2 O- or a single bond, more preferably a divalent group represented by -COO- or -OCO-.
[0039] In formula (1), W1 represents a single bond, -O-, -S-, -COO-, -OCO- or -OCOO-, preferably a divalent group represented by -O-, -COO- or -OCO-, and more preferably -O-.
[0040] In one embodiment of the present invention, in formula (1), Y1 is preferably a divalent group represented by -COO- or -OCO-, and W1 is preferably a divalent group represented by -O-, -COO- or -OCO-.
[0041] In formula (1), V1 and V2 each independently represent an alkanediyl group having 1 to 20 carbon atoms which may have a substituent. 2- can be replaced by -O-, -S-, -NH-, -COO-, -OCO- or -OCOO-. Examples of the alkane diyl represented by V1 and V2 include methylene, ethylene, propane-1,3-diyl, butane-1,3-diyl, butane-1,4-diyl, pentane-1,5-diyl, hexane-1,6-diyl, heptane-1,7-diyl, octane-1,8-diyl, decane-1,10-diyl, tetradecane-1,14-diyl and eicosane-1,20-diyl. The number of carbon atoms in the alkane diyl represented by V1 and V2 is preferably 2 to 18, more preferably 4 to 16, and even more preferably 6 to 16. From the viewpoint of the phase transition temperature, it is preferred that at least one -CH 2 - is replaced by -O-, -S-, -NH-, -COO-, -OCO- or -OCOO-. From the viewpoint of the dichroic ratio, it is preferred that V1 and V2 are alkanediyl groups having no substituent.
[0042] Examples of the substituent that the alkanediyl group may have include a cyano group and a halogen atom, and the hydrogen atoms contained in the alkanediyl group may be substituted with the above groups. In one embodiment of the present invention, the alkanediyl group is preferably unsubstituted, and more preferably an unsubstituted linear alkanediyl group.
[0043] In formula (1), U1 and U2 independently represent a hydrogen atom or a polymerizable group. Among them, at least one of U1 and U2 is a polymerizable group, and preferably U1 and U2 are both polymerizable groups. The so-called polymerizable group refers to a group that can participate in a polymerization reaction using active free radicals, acids, etc. generated by a polymerization initiator. As a polymerizable group, for example, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, (meth)acryloyl, (meth)acryloyloxy, oxacyclopropyl, oxetane, etc. can be cited. Among them, preferably (meth)acryloyl, (meth)acryloyloxy, vinyloxy, oxacyclopropyl and oxetane, more preferably (meth)acryloyloxy, and further preferably acryloyloxy.
[0044] The polymerizable group represented by U1 and the polymerizable group represented by U2 may be different from each other, but are preferably the same type of group. Preferably, at least one of U1 and U2 is a (meth)acryloyloxy group, more preferably both are (meth)acryloyloxy groups, and further preferably both are acryloyloxy groups.
[0045] In the polymerizable compound (1), the cyclohexane-1,4-diyl group is bonded to the group represented by V1 and the group represented by X1 via *-COO- (bonded to the cyclohexane-1,4-diyl group at *). The cyclohexane-1,4-diyl group may be a cis isomer or a trans isomer. Compared with the case where the cyclohexane-1,4-diyl group in formula (1) is bonded to the group represented by V1 and / or the group represented by X1 via -OCO- or -O-, the polymerizable compound (1) having the above structure has improved solubility in a solvent and can significantly reduce the phase transition temperature. In particular, this effect becomes significant compared with the case where the cyclohexane-1,4-diyl group is bonded to the group represented by V1 via -OCO- or -O-. The reason why the polymerizable compound (1) has excellent solubility in solvents and the effect of reducing the phase transition temperature is not necessarily clear, but it is believed that in the polymerizable compound (1) in which the cyclohexane ring is bonded to the adjacent group through *-COO- (bonded at *), the stacking (stack) of the molecules becomes weaker than when the cyclohexane ring is bonded to the adjacent group through an ether structure (-O-), and the flexibility of the molecules becomes higher. On the other hand, generally speaking, when the linearity of the molecules constituting the compound becomes lower, it tends to be difficult to ensure high liquid crystallinity and dichroic ratio. In the case where the bonding part of the cyclohexane ring and the group represented by V1 and X1 is an ester structure, the linearity of the molecule becomes easier to decrease than when the bonding part is an ether structure, but the polymerizable compound (1) achieves excellent solvent solubility and a lower phase transition temperature by taking advantage of the difference in the above-mentioned molecular structure, and can achieve a high dichroic ratio.
[0046] The polymerizable compound (1) is preferably a liquid crystal compound. The liquid crystal may be a thermotropic liquid crystal or a lyotropic liquid crystal, but when mixed with a dichroic pigment described later, a thermotropic liquid crystal is preferred. When the polymerizable compound (1) is a thermotropic liquid crystal compound, it may be a thermotropic liquid crystal compound showing a nematic liquid crystal phase, or it may be a thermotropic liquid crystal compound showing a smectic liquid crystal phase. In the case of forming a light absorption anisotropic film showing polarization performance, the liquid crystal state shown by the polymerizable compound (1) is preferably a smectic liquid crystal phase, and from the perspective of high performance, a high-order smectic phase is more preferred. Among them, a high-order smectic liquid crystal compound capable of forming a smectic B phase, a smectic D phase, a smectic E phase, a smectic F phase, a smectic G phase, a smectic H phase, a smectic I phase, a smectic J phase, a smectic K phase or a smectic L phase is more preferred, and a high-order smectic liquid crystal compound forming a smectic B phase, a smectic F phase or a smectic I phase is further preferred. When the liquid crystal phase formed by the polymerizable compound (1) is such a high-order smectic phase, a light absorption anisotropic film having higher polarization performance can be produced.
[0047] In the polymerizable compound (1), it is preferred that the portion represented by the formula (1A) in the formula (1) has an asymmetric structure because it is easy to exhibit smectic liquid crystal properties.
[0048] [Chemical formula 3]
[0049]
[0050] [In formula (1A), X1, Y1 and X2 have the same meanings as above, and * represents a bonding portion to V1 or W1 in formula (1)].
[0051] Examples of polymerizable compounds (1) in which a partial structure (1A) is an asymmetric structure include polymerizable compounds (1) having the following structures (1A-1) and (1A-2) in which both X1 and X2 in formula (1) are 1,4-phenylene, polymerizable compounds (1) having the following structures (1A-3) and (1A-4) in which X1 is cyclohexane-1,4-diyl and X2 is 1,4-phenylene, and polymerizable compounds (1) having the following structures (1A-5) and (1A-6) in which X1 is 1,4-phenylene and X2 is cyclohexane-1,4-diyl. In the following structures (1A-1) to (1A-6), * indicates a bonding portion to V1 or W1 in formula (1).
[0052] [Chemical formula 4]
[0053]
[0054] Specific examples of the polymerizable compound (1) include compounds represented by formula (1-1) to formula (1-24). The cyclohexane-1,4-diyl group contained in the polymerizable compound (1) is preferably a trans isomer.
[0055] [Chemical formula 5]
[0056]
[0057] [Chemical formula 6]
[0058]
[0059] [Chemical formula 7]
[0060]
[0061] The liquid phase-liquid crystal phase transition temperature of the polymerizable compound (1) is preferably 25°C or more and 150°C or less. When the phase transition temperature to the liquid crystal phase is within the above range, it is preferred from the viewpoints of easy industrial production and improved productivity. In the present invention, the liquid phase-liquid crystal phase transition temperature of the polymerizable compound (1) is usually 40°C or more, more preferably 50°C or more, and further preferably 60°C or more. Furthermore, from the viewpoint of productivity, it is more preferably 120°C or less, further preferably 110°C or less, and particularly preferably 100°C or less. From the viewpoint of productivity, the high-order smectic phase-smectic (Japanese: スメチクック) phase transition temperature of the polymerizable compound (1) is more preferably 100°C or less, further preferably 90°C or less, and particularly preferably 80°C or less. When the phase transition temperature of the polymerizable compound (1) is low, film formation can be achieved without exposure to high temperature conditions, and it can be expected that higher optical properties will be imparted to the obtained optical film.
[0062] The liquid crystal phase transition temperature can be measured using, for example, a polarizing microscope equipped with a temperature control stage, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analyzer (TG-DTA), or the like.
[0063] The polymerizable compound (1) can be produced by appropriately combining known organic synthesis reactions described in Methods of Organic Chemistry, Organic Reactions, Organic Syntheses, Comprehensive Organic Synthesis, New Experimental Chemistry Lectures, etc. (for example, condensation reaction, esterification reaction, Williamson etherification reaction, Ullmann reaction, Wittig reaction, Schiff base synthesis reaction, benzylation reaction, Sonogashira reaction, Suzuki-Miyaura reaction, Negishi reaction, Kumada reaction, Hiyama reaction, Buchwald-Hartwig reaction, Friedel-Crafts reaction, Heck reaction, aldol condensation reaction, etc.) according to its structure.
[0064] For example, a compound represented by formula (2) in which U1 is an acryloyloxy group can be produced by the following method. It should be noted that V1, V2, X1, X2, Y1, W1 and U2 in the following formulas (2) to (4), (6) and (7) each have the same meaning as those in formula (1), and are structures corresponding to V1, V2, X1, X2, Y1, W1 and U2 of the target polymerizable compound (1).
[0065] [Chemical formula 8]
[0066]
[0067] First, 1,4-cyclohexanedicarboxylic acid and a compound represented by formula (3) (hereinafter also referred to as "compound (3)") are reacted under basic conditions (hereinafter also referred to as "step (i-1)") to obtain a compound represented by formula (4) (hereinafter also referred to as "compound (4)"):
[0068] [Chemical formula 9]
[0069] HO-V1-X3 (3)
[0070] [In formula (3),
[0071] V1 represents an alkanediyl group having 1 to 20 carbon atoms which may have a substituent, and the -CH 2 - can be replaced by -O-, -S-, -NH-, -COO-, -OCO- or -OCOO-,
[0072] X3 represents a halogen atom];
[0073] [Chemical formula 10]
[0074]
[0075] Step (i-1) is usually carried out in the presence of a basic compound. Examples of the basic compound include metal carbonates such as sodium carbonate, potassium carbonate, cesium carbonate, calcium carbonate, and magnesium carbonate; metal bicarbonates such as lithium bicarbonate, sodium bicarbonate, potassium bicarbonate, and cesium bicarbonate; and metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide, cesium hydroxide, and calcium hydroxide.
[0076] The amount of the basic compound in step (i-1) is preferably 1.4 mol or more, more preferably 1.8 mol or more, and is preferably 3 mol or less, more preferably 2.5 mol or less, based on 1 mol of compound (3).
[0077] The amount of 1,4-cyclohexanedicarboxylic acid used in the reaction of step (i-1) is preferably 1.0 mol or more, more preferably 1.1 mol or more, and even more preferably 1.2 mol or more, and is preferably 2.0 mol or less, more preferably 1.7 mol or less, and even more preferably 1.5 mol or less, relative to 1 mol of compound (3). When the amount of 1,4-cyclohexanedicarboxylic acid is greater than the lower limit and less than the upper limit, by-products are less likely to be generated.
[0078] The reaction of 1,4-cyclohexanedicarboxylic acid with compound (3) in step (i-1) is usually carried out in a solvent. Examples of the solvent include ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl amyl ketone or methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane or heptane; aromatic hydrocarbon solvents such as toluene, xylene, benzene or chlorobenzene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; ester solvents such as ethyl lactate; halogenated hydrocarbon solvents such as chloroform and dichloromethane; aprotic polar solvents such as dimethyl sulfoxide, N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, hexamethylphosphoric triamide, etc. These solvents may be used alone or in combination.
[0079] The amount of the solvent used is not particularly limited, but is preferably 0.5 to 50 parts by mass, more preferably 1 to 30 parts by mass, and even more preferably 1 to 20 parts by mass, based on 1 part by mass of the total of 1,4-cyclohexanedicarboxylic acid and compound (3).
[0080] The reaction conditions in step (i-1) can be appropriately determined. From the viewpoint of reaction yield and productivity, the reaction temperature is preferably 60 to 150°C, more preferably 80 to 120°C. In addition, the reaction time is preferably 1 minute to 72 hours, more preferably 1 to 48 hours, and further preferably 1 to 24 hours. By reacting 1,4-cyclohexanedicarboxylic acid with the alcohol compound (3) within the above-mentioned temperature range and time range, the reaction yield is easily improved. The degree of progress of the reaction can be confirmed by analytical means such as high performance liquid chromatography, thin layer chromatography, and gas chromatography.
[0081] After the reaction between 1,4-cyclohexanedicarboxylic acid and compound (3) is completed, compound (4) can be obtained by performing treatments and operations such as post-treatments such as filtration, neutralization, extraction, and water washing, and separation treatments such as distillation and crystallization.
[0082] Compound (4) can also be obtained by subjecting 1,4-cyclohexanedicarboxylic acid to an esterification reaction with a compound represented by formula (5) (hereinafter also referred to as “compound (5)”) (hereinafter also referred to as “step (i-2)”).
[0083] [Chemical formula 11]
[0084]
[0085] The esterification reaction between 1,4-cyclohexanedicarboxylic acid and compound (5) is preferably carried out in the presence of a condensing agent. By carrying out the esterification reaction in the presence of a condensing agent, the esterification reaction can be carried out efficiently and rapidly.
[0086] Examples of the condensing agent include 1-cyclohexyl-3-(2-morpholinoethyl)carbodiimide methyl p-toluenesulfonate, dicyclohexylcarbodiimide, diisopropylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (water-soluble carbodiimide: commercially available as WSC), bis(2,6-diisopropylphenyl)carbodiimide, imide, and carbodiimide compounds such as bis(trimethylsilyl)carbodiimide, 2-methyl-6-nitrobenzoic anhydride, 2,2'-carbonylbis-1H-imidazole, 1,1'-oxalyldiimidazole, diphenylphosphoryl azide, 1-(4-nitrobenzenesulfonyl)-1H-1,2,4-triazole, 1H-benzotriazol-1-yloxytripyrrolidinophosphonium hexafluorophosphate, 1H-benzotriazol-1-yloxy Tris(dimethylamino)phosphonium hexafluorophosphate, N,N,N',N'-tetramethyl-O-(N-succinimidyl)uronium tetrafluoroborate, N-(1,2,2,2-tetrachloroethoxycarbonyloxy)succinimide, N-benzyloxycarbonylsuccinimide, O-(6-chlorobenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate, O-(6-chlorobenzotriazol-1-yl) )-N,N,N',N'-tetramethyluronium hexafluorophosphate, 2-bromo-1-ethylpyridinium tetrafluoroborate, 2-chloro-1,3-dimethylimidazolinium chloride, 2-chloro-1,3-dimethylimidazolinium hexafluorophosphate, 2-chloro-1-methylpyridinium iodide, 2-chloro-1-methylpyridinium p-toluenesulfonate, 2-fluoro-1-methylpyridinium p-toluenesulfonate and pentachlorophenyl trichloroacetate, etc.
[0087] The condensing agent is preferably a carbodiimide compound, 2,2'-carbonylbis-1H-imidazole, 1H-benzotriazol-1-yloxytripyrrolidinylphosphonium hexafluorophosphate, 1H-benzotriazol-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate, N,N,N',N'-tetramethyl-O-(N-succinimidyl)uronium tetrafluoroborate, O-(6-chlorobenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, 2-chloro-1,3-dimethylimidazolinium chloride and 2-chloro-1-methylpyridinium iodide, and more preferably a carbodiimide compound from the viewpoint of economic efficiency.
[0088] Among the carbodiimide compounds, dicyclohexylcarbodiimide, diisopropylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (water-soluble carbodiimide) and bis(2,6-diisopropylphenyl)carbodiimide are preferred from the viewpoints of reactivity, cost and a wide range of choices of usable solvents.
[0089] The amount of the condensing agent used is usually 1.0 to 1.5 mol based on 1 mol of compound (5).
[0090] In the esterification reaction, additives such as N-hydroxysuccinimide, benzotriazole, p-nitrophenol, 3,5-dibutyl-4-hydroxytoluene, etc. may be further added. The amount of these additives used is preferably 0.01 to 0.1 mol based on 1 mol of compound (5).
[0091] In addition, the esterification reaction can be carried out in the presence of a catalyst. Examples of the catalyst include N,N-dimethylaminopyridine, N,N-dimethylaniline, dimethylammonium pentafluorobenzenesulfonate, and the like. Among them, N,N-dimethylaminopyridine and N,N-dimethylaniline are preferred, and N,N-dimethylaminopyridine is more preferred. When a catalyst is used, the amount used is preferably 0.01 to 0.1 mol relative to 1 mol of compound (5).
[0092] The amount of 1,4-cyclohexanedicarboxylic acid used for the reaction in step (i-2) is preferably 1.0 mol or more, more preferably 1.1 mol or more, and further preferably 1.2 mol or more, relative to 1 mol of compound (3), and is preferably 2.0 mol or less, more preferably 1.7 mol or less, and further preferably 1.5 mol or less. When the amount of 1,4-cyclohexanedicarboxylic acid is above the lower limit and below the upper limit, the yield of compound (4) becomes good, and by-products are less likely to be generated, so that the compound (4) can be produced with good productivity.
[0093] The esterification reaction is usually carried out in a solvent. Examples of the solvent include the same solvents as those exemplified as the solvents that can be used in the reaction between 1,4-cyclohexanedicarboxylic acid and the compound (3) in step (i-1).
[0094] The amount of the solvent used is not particularly limited, but is preferably 0.5 to 50 parts by mass, more preferably 1 to 30 parts by mass, and even more preferably 1 to 20 parts by mass, based on 1 part by mass of the total of 1,4-cyclohexanedicarboxylic acid and compound (5).
[0095] The conditions of the esterification reaction can be appropriately determined. From the viewpoint of reaction yield and productivity, the temperature of the esterification reaction is preferably -20 to 100 ° C, more preferably -10 to 60 ° C, and further preferably -5 to 50 ° C. In addition, the time of the esterification reaction is preferably 1 minute to 72 hours, more preferably 1 to 48 hours, and further preferably 1 to 24 hours. By carrying out the esterification reaction within the above-mentioned temperature range and time range, the reaction yield is easily improved. The degree of progress of the reaction can be confirmed by analytical means such as high performance liquid chromatography, thin layer chromatography, and gas chromatography.
[0096] After the reaction between 1,4-cyclohexanedicarboxylic acid and compound (5) is completed, compound (4) can be obtained by performing treatments and operations such as filtration, neutralization, extraction, post-treatments such as water washing, and separation treatments such as distillation and crystallization.
[0097] The compounds (3) and (5) used in the reactions of steps (i-1) and (i-2) can be produced by appropriately combining the various known organic synthesis reactions described above based on their structures. Alternatively, commercially available products may be used.
[0098] Next, the compound (4) is reacted with an acid chloride represented by formula (6) to obtain a compound represented by formula (7) (hereinafter also referred to as “compound (7)”) (hereinafter also referred to as “step (ii)”), and then the obtained compound (7) is subjected to an esterification reaction with a compound represented by formula (8) (hereinafter also referred to as “compound (8)”) (hereinafter also referred to as “step (iii)”) to obtain the polymerizable compound (1) represented by formula (2):
[0099] [Chemical formula 12]
[0100]
[0101] [In formula (6), Y represents a hydrogen atom or a methyl group];
[0102] [Chemical formula 13]
[0103]
[0104] [Chemical formula 14]
[0105] HO-X1-Y1-X2-W1-V2-U2 (8).
[0106] Step (ii) is a step of acryloylating the compound (4). The acid chloride can be produced by a conventionally known organic synthesis method, but commercially available (meth)acryloyl chloride can also be used.
[0107] In step (ii), the acid chloride is present in an amount of preferably 1.0 mol or more and 15.0 mol or less relative to 1 mol of compound (4). When the acid chloride is present in an amount within the above range, the reaction with compound (4) is easily carried out, and compound (6) can be obtained in a high yield. The acid halide is present in an amount of more preferably 1.05 mol or more, further preferably 1.1 mol or more, and more preferably 5.0 mol or less, further preferably 3.0 mol equivalents relative to 1 mol of compound (4).
[0108] Step (ii) is usually carried out in the presence of a basic substance. Examples of the basic substance include amines such as trimethylamine, triethylamine, N,N-diisopropylethylamine, N,N-dimethylaniline, and N,N-diethylaniline. In particular, from the viewpoint of easily improving the yield, it is preferred to carry out the reaction of compound (4) with the acid chloride in the presence of an aromatic amine.
[0109] In the reaction of compound (4) and the acid chloride, the alkaline substance is present in an amount of preferably 1.0 mol or more and 15.0 mol or less relative to 1 mol of compound (4). When the alkaline substance is present in an amount within the above range, the reaction of compound (4) and the acid chloride is easily promoted, and compound (7) can be obtained in a sufficiently high yield. The alkaline substance is present in an amount of more preferably 1.1 mol or more, further preferably 1.2 mol or more, and more preferably 10.0 mol or less, further preferably 5.0 mol or less relative to 1 mol of compound (4).
[0110] In step (ii), the reaction of the compound (4) and the acid chloride is preferably carried out in the presence of a solvent. Examples of the solvent include the same solvents as those exemplified as the solvents that can be used in the reaction of 1,4-cyclohexanedicarboxylic acid and the alcohol compound (3).
[0111] The amount of the solvent used is not particularly limited. In order to fully dissolve each compound and allow the reaction to proceed efficiently, it is usually 2 parts by mass or more, preferably 3 parts by mass or more, relative to 1 part by mass of compound (4). In order to avoid the use of excessive solvent, it is usually 100 parts by mass or less, preferably 70 parts by mass or less, and more preferably 50 parts by mass or less.
[0112] For the reaction of compound (4) and acyl chloride, additives can be used as needed, for example, in order to prevent polymerization, it can be carried out in the presence of a polymerization inhibitor. As a polymerization inhibitor, for example, 2,6-di-tert-butyl-p-cresol (BHT), 2,2'-methylenebis (6-tert-butyl-p-cresol), triphenyl phosphite, tris (nonylphenyl) phosphite, phenothiazine, etc. can be cited. When using a polymerization inhibitor, its addition amount is preferably 0.005 moles or more relative to 1 mole of compound (4), more preferably 0.01 moles or more, and preferably 0.5 moles or less.
[0113] In step (ii), the reaction of the compound (4) and the acid chloride can be carried out, for example, by adding dropwise the acid chloride to a mixture containing the compound (4) and a basic substance and, if necessary, a solvent and an additive.
[0114] The conditions in the above reaction can be appropriately determined according to the types of the compounds used, the reaction scale, etc. For example, the reaction temperature of compound (4) and the acid chloride is preferably -10°C to 25°C, more preferably -5°C to 25°C. When the reaction temperature is within the above range, the reaction of compound (4) and the acid chloride is easy to proceed, and since it is a mild condition, it is easy to obtain the target compound more safely.
[0115] The reaction time may be determined according to the types and ratio of the compounds used, the temperature, etc., and although it depends on the reaction scale, etc., it is preferably 10 minutes to 24 hours, and more preferably 10 minutes to 12 hours.
[0116] After completion of the reaction, compound (7) can be obtained by performing treatments and operations such as post-treatments such as filtration, neutralization, extraction, and water washing, and separation treatments such as distillation and crystallization.
[0117] The compound (8) used in the reaction of step (iii) can be produced by appropriately combining the various known organic synthesis reactions described above based on its structure.
[0118] The esterification reaction of compound (7) and compound (8) is preferably carried out in the presence of a condensing agent. By carrying out the esterification reaction in the presence of a condensing agent, the esterification reaction can be carried out efficiently and rapidly. As the condensing agent, the same condensing agent as the condensing agent that can be used in the esterification reaction of 1,4-cyclohexanedicarboxylic acid and compound (5) can be cited.
[0119] The amount of the condensing agent used is usually 0.8 to 1.2 mol based on 1 mol of compound (7).
[0120] In the esterification reaction of compound (7) and compound (8), the additives and catalysts exemplified in the esterification reaction of 1,4-cyclohexanedicarboxylic acid and compound (5) can be used. When the additives and catalysts are used, the amounts thereof are preferably 0.01 to 0.1 mol, respectively, based on 1 mol of compound (7).
[0121] The esterification reaction between the compound (7) and the compound (8) is usually carried out in a solvent. Examples of the solvent include the same solvents as those exemplified as the solvents that can be used in the reaction between 1,4-cyclohexanedicarboxylic acid and the compound (3) in step (i-1).
[0122] The amount of the solvent used is not particularly limited, but is preferably 1 to 50 parts by mass, more preferably 1 to 40 parts by mass, and even more preferably 1 to 30 parts by mass, based on 1 part by mass of the total of Compound (7) and Compound (8).
[0123] The conditions of the esterification reaction can be appropriately determined. From the viewpoint of reaction yield and productivity, the temperature of the esterification reaction is preferably -20 to 60°C, more preferably -20 to 40°C. In addition, the time of the esterification reaction is preferably 1 minute to 72 hours, more preferably 1 to 48 hours, and further preferably 1 to 24 hours. By carrying out the esterification reaction within the above-mentioned temperature range and time range, the reaction yield is easily improved. The degree of progress of the reaction can be confirmed by analytical means such as high performance liquid chromatography, thin layer chromatography, and gas chromatography.
[0124] After the reaction is completed, the desired polymerizable compound (1) can be isolated by, as necessary, performing post-treatments such as filtration, neutralization, extraction, and water washing, and separation treatments such as distillation and crystallization, and other treatments and operations that can be used in organic synthetic chemistry.
[0125] The structure of the obtained compound can be identified by NMR spectrum, IR spectrum, mass spectrum measurement, elemental analysis, and the like.
[0126] In formula (1), the polymerizable compound (1) of the present invention, in which the cyclohexane ring is bonded to the adjacent groups V1 and X1 respectively through *-COO-, can be produced using relatively inexpensive 1,4-cyclohexanedicarboxylic acid as a starting material, and the production process can also be simplified. Therefore, compared with conventional polymerizable compounds having a structure in which a cyclohexane-1,4-diyl group is bonded to a group represented by V1 and / or a group represented by X1 through -OCO- or -O-, it is also advantageous in terms of production cost, production efficiency, etc.
[0127] <Polymerizable composition>
[0128] The present invention also targets a polymerizable composition comprising the polymerizable compound (1) of the present invention and a dichroic dye. As described above, the polymerizable compound (1) of the present invention has a low phase transition temperature and excellent solvent solubility, and is particularly suitable as a material for forming a light absorption anisotropic film (polarizing film) having a high dichroic ratio.
[0129] The content of the polymerizable compound (1) in the polymerizable composition of the present invention is preferably 40 to 99.9% by mass, more preferably 60 to 99% by mass, and further preferably 70 to 99% by mass relative to the solid content of the polymerizable composition. When the content of the polymerizable compound is within the above range, there is a tendency for the orientation of the polymerizable compound (1) to become higher. It should be noted that in this specification, the solid content of the polymerizable composition refers to the total amount of the components after removing volatile substances such as solvents from the composition. Hereinafter, regarding the solid content in other compositions, it also refers to the total amount of the components after removing volatile substances such as solvents from the composition as the object.
[0130] In the present invention, the polymerizable composition may contain other polymerizable compounds other than the polymerizable compound (1) of the present invention. In one embodiment of the present invention, from the viewpoint of obtaining a light absorption anisotropic film with a high degree of orientation order, the proportion of the polymerizable compound (1) relative to the total mass of all polymerizable compounds contained in the polymerizable composition is preferably 51% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more.
[0131] The so-called dichroic pigment refers to a pigment having a different property of absorbance in the long axis direction of the molecule and absorbance in the short axis direction. As the dichroic pigment contained in the polymerizable composition of the present invention, it is preferred to have a characteristic of absorbing visible light, and more preferably a dichroic pigment having an absorption maximum wavelength (λMAX) in the range of 380 to 680 nm. As such a dichroic pigment, for example, acridine pigments, oxazine pigments, cyanine pigments, naphthalene pigments, azo pigments and anthraquinone pigments can be cited, among which azo pigments are preferred. As azo pigments, monoazo pigments, disazo pigments, triazo pigments, tetrazo pigments and stilbene azo pigments can be cited, preferably disazo pigments and triazo pigments. These dichroic pigments can be appropriately selected from substances known in the art for use. The dichroic pigment can be alone or in combination, but in order to be absorbed in the entire visible light region, it is preferred to combine two or more dichroic pigments, and more preferably to combine three or more dichroic pigments. In particular, by mixing two or more dichroic pigments with different absorption wavelengths, it is possible to produce light absorption anisotropic films of various hues, and it is possible to produce light absorption anisotropic films that have absorption in the entire visible light region. By producing a light absorption anisotropic film with such absorption characteristics, it can be used in various applications.
[0132] Examples of the azo dye include compounds having the following structures.
[0133] T 1 -A 1 (-N=NA 2 ) p -N=NA 3 -T 2
[0134] [Where A 1 and A 2 and A 3 each independently represents a 1,4-phenylene group which may have a substituent, a naphthalene-1,4-diyl group which may have a substituent, a benzoic acid phenyl ester group which may have a substituent, a 4,4′-stilbenylene group which may have a substituent, or a divalent heterocyclic group which may have a substituent, T 1 and T 2is an electron withdrawing group or an electron donating group and is located at a position substantially 180° relative to the azo bond plane. p represents an integer of 0 to 4. When p is 2 or more, each A 2 They may be the same or different from each other. In the range showing absorption in the visible light region, the -N=N- bond may be replaced by a -C=C-, -COO-, -NHCO-, or -N=CH- bond.]
[0135] The content of the dichroic pigment (the total amount when containing multiple kinds) is generally 1 to 60 parts by mass, preferably 1 to 40 parts by mass, and more preferably 1 to 20 parts by mass relative to 100 parts by mass of all polymerizable compounds contained in the polymerizable composition from the viewpoint of obtaining good light absorption characteristics. When the content of the dichroic pigment is less than this range, light absorption tends to become insufficient, and there is a possibility that sufficient polarization performance cannot be obtained. In addition, when it is more than this range, there is a tendency to easily hinder the orientation of liquid crystal molecules.
[0136] Generally, a polymerizable compound showing smectic liquid crystal properties has a high viscosity. Therefore, the polymerizable composition preferably further contains a solvent from the viewpoint of improving the coating properties of the polymerizable composition and facilitating the formation of a cured film of the polymerizable composition.
[0137] The solvent used for the polymerizable composition can be appropriately selected according to the solubility of the polymerizable compound (1) and the dichroic dye used. Specifically, the same solvents as those exemplified as the solvents that can be used in the production of the polymerizable compound (1) can be cited. The content of the solvent is preferably 100 to 1900 parts by mass, more preferably 150 to 900 parts by mass, and further preferably 180 to 600 parts by mass relative to 100 parts by mass of the solid content of the polymerizable composition.
[0138] The polymerizable composition may contain a polymerization initiator. A polymerization initiator is a compound that can initiate a polymerization reaction of a polymerizable compound, and is preferably a photopolymerization initiator in terms of being able to initiate a polymerization reaction under lower temperature conditions. Specifically, a photopolymerization initiator that can generate active free radicals or acids by the action of light can be cited, and from the viewpoint of being independent of the phase state of thermotropic liquid crystals, a photopolymerization initiator that generates free radicals by the action of light is preferred. The polymerization initiator can be used alone or in combination of two or more.
[0139] As the photopolymerization initiator, a known photopolymerization initiator can be used. For example, as a photopolymerization initiator that generates active radicals, there are self-cleavage type photopolymerization initiators and hydrogen abstraction type photopolymerization initiators.
[0140] As the self-cleaving type photopolymerization initiator, self-cleaving type benzoin compounds, acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, oxime ester compounds, acylphosphine oxide compounds, azo compounds, etc. can be used. In addition, as the hydrogen abstraction type photopolymerization initiator, hydrogen abstraction type benzophenone compounds, alkylphenyl ketone compounds, benzoin ether compounds, benzyl ketal compounds, dibenzosuberone compounds, anthraquinone compounds, xanthone compounds, thioxanthone compounds, halogenated acetophenone compounds, dialkoxyacetophenone compounds, halogenated bisimidazole compounds, halogenated triazine compounds, triazine compounds, etc. can be used.
[0141] As the photopolymerization initiator that generates an acid, iodonium salts, sulfonium salts, and the like can be used.
[0142] Among them, from the viewpoint of preventing the dissolution of the pigment, a reaction at a low temperature is preferred, and from the viewpoint of reaction efficiency at a low temperature, a self-cleavage type photopolymerization initiator is preferred, and acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, and oxime ester compounds are particularly preferred.
[0143] Specific examples of the photopolymerization initiator include the following.
[0144] Benzoin compounds such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether and benzoin isobutyl ether;
[0145] Hydroxyacetophenone compounds such as 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1,2-diphenyl-2,2-dimethoxyethane-1-one, 2-hydroxy-2-methyl-1-〔4-(2-hydroxyethoxy)phenyl〕propane-1-one, 1-hydroxycyclohexylphenylketone and oligomers of 2-hydroxy-2-methyl-1-〔4-(1-methylvinyl)phenyl〕propane-1-one;
[0146] α-Aminoacetophenone compounds such as 2-methyl-2-morpholino-1-(4-methylthiophenyl)propane-1-one and 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butane-1-one;
[0147] Oxime ester compounds such as 1-[4-(phenylthio)-1,2-octanedione 2-(O-benzoyl oxime) and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime); acyl phosphine oxide compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide;
[0148] Benzophenone compounds such as benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetrakis(tert-butylperoxycarbonyl)benzophenone and 2,4,6-trimethylbenzophenone;
[0149] Dialkoxyacetophenone compounds such as diethoxyacetophenone;
[0150] 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)vinyl]-1,3,5 The photopolymerization initiator may be selected from the above-mentioned photopolymerization initiators, for example, in accordance with the relationship with the polymerizable compound (1).
[0151] In addition, a commercially available photopolymerization initiator can be used. Examples of commercially available polymerization initiators include Irgacure (registered trademark) 907, 184, 651, 819, 250, 369, 379, 127, 754, OXE01, OXE02, and OXE03 (manufactured by BASF); Omnirad BCIM, Esacure 1001M, and Esacure KIP160 (manufactured by IDM Resins BV); SEIKUOL (registered trademark) BZ, Z, and BEE (manufactured by Seiko Chemical Co., Ltd.); Kayacure (registered trademark) BP100 and UVI-6992 (manufactured by DOW Chemical Company); ADEKA OPTOMER SP-152, N-1717, N-1919, SP-170, and ADEKA ARKLS NCI-831, ADEKA ARKLS NCI-930 (manufactured by ADEKA Corporation); TAZ-A and TAZ-PP (manufactured by Nippon Siber Hegner Co., Ltd.); and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.); and the like.
[0152] The content of the polymerization initiator in the polymerizable composition is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, further preferably 1 to 8 parts by mass, and particularly preferably 1 to 6 parts by mass, relative to 100 parts by mass of all polymerizable compounds contained in the polymerizable composition. When the content of the polymerization initiator is within the above range, the polymerization reaction can be carried out without significantly disturbing the orientation of the polymerizable compound (1).
[0153] The polymerizable composition may contain a leveling agent. The leveling agent has the function of adjusting the fluidity of the polymerizable composition and making the coating film obtained by applying the composition flatter. Specifically, a surfactant can be mentioned. As the leveling agent, organic modified silicone oil-based, polyacrylate-based and perfluoroalkyl-based leveling agents can be mentioned. Among them, polyacrylate-based and perfluoroalkyl-based leveling agents are preferred. The leveling agent can be used alone or in combination of two or more.
[0154] Examples of polyacrylate-based leveling agents include BYK-350, BYK-352, BYK-353, BYK-354, BYK-355, BYK-358N, BYK-361N, BYK-380, BYK-381, and BYK-392 (BYK Chemie).
[0155] Examples of perfluoroalkyl leveling agents include "MEGAFACE (registered trademark) R-08", MEGAFACE "R-30", MEGAFACE "R-90", MEGAFACE "F-410", MEGAFACE "F-411", MEGAFACE "F-443", MEGAFACE "F-445", MEGAFACE "F-470", MEGAFACE "F-471", MEGAFACE "F-4 "77", MEGAFACE "F-479", MEGAFACE "F-482" and MEGAFACE "F-483" (DIC (KK)); "Surflon (registered trademark) S-381", Surflon "S-382", Surflon "S-383", Surflon "S-393", Surflon "SC-101", Surflon "SC-105", "KH-40" and "SA-100" (AGC Seimi Chemical Co., Ltd.); "E1830", "E5844" (Daikin Fine Chemical Kenkyusho, KK); "EFTOP EF301", "EFTOP EF303", "EFTOP EF351" and "EFTOPEF352" (Mitsubishi Materials Electronic Chemicals Co., Ltd.).
[0156] When the polymerizable composition contains a leveling agent, the content thereof is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of all polymerizable compounds contained in the polymerizable composition. When the content of the leveling agent is within the above range, the polymerizable compound (1) tends to be easily oriented horizontally, and the obtained light absorption anisotropic film tends to be smoother.
[0157] The polymerizable composition may contain other additives other than the leveling agent. Examples of other additives include photosensitizers, antioxidants, mold release agents, stabilizers, colorants such as bluing agents, flame retardants, and lubricants. When other additives are contained, the content of the additives is preferably more than 0% and less than 20% by mass, more preferably more than 0% and less than 10% by mass, relative to the solid content of the polymerizable composition.
[0158] The polymerizable composition can be produced by a conventionally known production method, and can usually be produced by mixing and stirring the polymerizable compound (1) and the dichroic dye, and, if necessary, a solvent, a polymerization initiator, and the above-mentioned additives.
[0159] In one embodiment of the present invention, the liquid phase-liquid crystal phase transition temperature in the polymerizable composition of the present invention containing the polymerizable compound (1) is preferably 25°C or more and 150°C or less. When the phase transition temperature to the liquid crystal phase is within the above range, it is preferred from the viewpoints of easy industrial production and improved productivity. In the present invention, the liquid phase-liquid crystal phase transition temperature is usually 40°C or more, more preferably 50°C or more, and further preferably 60°C or more. In addition, from the viewpoint of productivity, it is more preferably 120°C or less, more preferably 110°C or less, and particularly preferably 100°C or less. The nematic phase-smectic phase transition temperature is more preferably 100°C or less, and further preferably 95°C or less from the viewpoint of productivity. In the polymerizable composition of the present invention containing the polymerizable compound (1), the liquid crystal phase transition temperature in the state mixed with the dichroic dye is also easily reduced. When the phase transition temperature of the polymerizable composition is lowered, film formation can be achieved without exposure to high temperature conditions, and it can be expected that higher optical properties will be imparted to the obtained optical film.
[0160] The liquid crystal phase transition temperature can be measured, for example, using a polarizing microscope equipped with a temperature control stage, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analyzer (TG-DTA), etc. In the case of containing a polymerizable compound (1) and a dichroic dye, and optionally other liquid crystal compounds, the phase transition temperature refers to a temperature measured using a mixture of the polymerizable compound (1) constituting the polymerizable composition, the dichroic dye, and the other liquid crystal compounds in the same ratio as the composition in the polymerizable composition.
[0161] <Optical film>
[0162] For example, an optical film having polarizing properties can be obtained by a method comprising the following steps: forming a coating film of the polymerizable composition of the present invention on a substrate or an oriented film; removing the solvent from the coating film; raising the temperature to a temperature above the temperature at which the polymerizable compound (1) undergoes a phase transition to a liquid phase, and then lowering the temperature to transform the polymerizable compound (1) into a liquid crystal phase (e.g., a smectic phase); and polymerizing (curing) the polymerizable compound (1) while maintaining the aforementioned liquid crystal phase. The present invention also targets an optical film comprising a polymer of the polymerizable compound (1) or a cured product of the polymerizable composition of the present invention.
[0163] The coating film of the polymerizable composition can be formed by applying the polymerizable composition on a substrate, an alignment film, or the like.
[0164] As the substrate, for example, there can be mentioned a glass substrate, and a film substrate composed of polyolefins such as polyethylene, polypropylene, and norbornene polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide and polyphenylene ether, etc.
[0165] The alignment film is an alignment film with an alignment control force that allows the polymerizable compound (1) to be aligned in a desired direction. The alignment film facilitates the alignment of the polymerizable compound (1) in the liquid crystal. The state of the liquid crystal alignment, such as horizontal alignment, vertical alignment, mixed alignment, and tilted alignment, varies depending on the properties of the alignment film and the polymerizable compound (1), and the combination thereof can be selected arbitrarily. For example, if the alignment film is a material that exhibits horizontal alignment as an alignment control force, the polymerizable compound (1) can form a horizontal alignment or a mixed alignment, and if it is a material that exhibits vertical alignment, the polymerizable compound (1) can form a vertical alignment or a tilted alignment. Expressions such as horizontal and vertical indicate the direction of the long axis of the aligned polymerizable compound (1) with the plane of the light absorption anisotropic film as a reference. For example, the so-called horizontal alignment means that the long axis of the aligned polymerizable compound (1) is in a direction horizontal to the plane of the light absorption anisotropic film, and the so-called vertical alignment means that the long axis of the aligned polymerizable compound (1) is in a direction vertical to the plane of the light absorption anisotropic film. It should be noted that the vertical mentioned here refers to 90°±20° relative to the plane of the light absorption anisotropic film.
[0166] In order to obtain polarization performance on the XY plane, the polymerizable compound (1) and the dichroic dye can be horizontally oriented relative to the plane of the light absorption anisotropic film. In order to obtain polarization performance in the Z direction (thickness direction of the light absorption anisotropic film), the polymerizable compound (1) and the dichroic dye can be vertically oriented relative to the plane of the light absorption anisotropic film.
[0167] The orientation control force can be arbitrarily adjusted by the surface state and rubbing conditions when the orientation film is formed of an orientation polymer, and can be arbitrarily adjusted by polarized light irradiation conditions, etc. when the orientation film is formed of a photo-orientation polymer. In addition, the liquid crystal orientation can also be controlled by selecting the physical properties such as the surface tension and liquid crystal properties of the polymerizable compound (1).
[0168] As the alignment film formed between the substrate and the light absorption anisotropic film, it is preferred that the alignment film is insoluble in the solvent used when forming the light absorption anisotropic film on the alignment film and has heat resistance in the heating treatment for removing the solvent and aligning the liquid crystal. As the alignment film, an alignment film formed of an aligning polymer, a photoalignment film, a groove alignment film, a stretched film stretched in the alignment direction, etc. can be cited.
[0169] The substrate and the alignment film can be appropriately selected and used from known materials that can be used in the production of conventional optical films, depending on the application of the optical film, the performance desired for the light absorption anisotropic film, and the like.
[0170] Examples of methods for coating a polymerizable composition on a substrate include extrusion coating, direct gravure coating, reverse gravure coating, CAP coating, slit coating, micro gravure coating, die coating, and inkjet. In addition, examples include methods for coating using a coating machine such as a dip coater, a rod coater, or a spin coater. Among them, in the case of continuous coating in a roll-to-roll form, a coating method based on a micro gravure coating method, an inkjet method, a slit coating method, or a die coating method is preferred, and in the case of coating on a monolithic substrate such as glass, a spin coating method having high uniformity is preferred.
[0171] Next, the solvent is removed by drying or the like under conditions where the polymerizable compound (1) contained in the coating film obtained from the polymerizable composition does not solidify (polymerize) to form a dried coating film. Examples of the drying method include natural drying, ventilation drying, heating drying, and reduced pressure drying.
[0172] Furthermore, in order to make the polymerizable compound (1) phase-transition to a liquid phase, the temperature is raised to a temperature above the temperature at which the polymerizable compound (1) phase-transitions to a liquid phase, and then the temperature is lowered to make the polymerizable compound (1) phase-transition to a liquid crystal phase (smectic phase). The above phase transition may be performed after the solvent in the coating film is removed, or may be performed simultaneously with the removal of the solvent.
[0173] The polymerizable compound (1) is cured (polymerized) while maintaining the liquid crystal state of the polymerizable compound (1), thereby forming a light absorption anisotropic film as a cured product of the polymerizable composition. As a curing method, photopolymerization is preferred. In photopolymerization, the light used to irradiate the dried coating film is appropriately selected according to the type of the polymerizable compound (1) contained in the dried coating film (especially the type of the polymerizable group possessed by the polymerizable compound), the type of polymerization initiator and their amount, etc. As specific examples thereof, one or more lights selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α rays, β rays and γ rays, and active electron beams can be cited. Among them, ultraviolet light is preferred in terms of easy control of the progress of the polymerization reaction and the ability to use a device widely used in the art as a photopolymerization device. It is preferred that the types of the polymerizable compound (1) and the polymerization initiator contained in the polymerizable composition are pre-selected in a manner that allows photopolymerization using ultraviolet light. In addition, during polymerization, the polymerization temperature can also be controlled by irradiating the dried coating film while cooling it using appropriate cooling means.
[0174] As the light source of the aforementioned active energy rays, there can be mentioned low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting light in the wavelength range of 380 to 440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, etc.
[0175] UV radiation intensity is usually 10 to 3,000 mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in the wavelength region effective for activating the photopolymerization initiator. The irradiation time is usually 0.1 seconds to 10 minutes, preferably 1 second to 5 minutes, more preferably 5 seconds to 3 minutes, and even more preferably 10 seconds to 1 minute. When irradiation is performed once or multiple times with such ultraviolet irradiation intensity, the cumulative light amount is usually 10 to 3,000 mJ / cm 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 When the accumulated light amount is within the above range, the polymerizable compound can be sufficiently cured, and the coloration suppression effect in the obtained light absorption anisotropic film is excellent.
[0176] By photopolymerization, the polymerizable compound (1) is cured (polymerized) while maintaining a liquid crystal phase, particularly a smectic phase, preferably a high-order smectic phase, to form a light absorption anisotropic film. The light absorption anisotropic film (polarizing film) obtained by curing (polymerizing) the polymerizable compound (1) while maintaining a liquid crystal state of a smectic phase has the advantage of having higher polarization performance than conventional host-guest type polarizing films, i.e., light absorption anisotropic films formed in a liquid crystal state of a nematic phase, due to the effect of the aforementioned dichroic dye. In addition, it has the advantage of having excellent strength compared to a film coated with only a dichroic dye or a lyotropic liquid crystal.
[0177] The thickness of the light absorption anisotropic film can be appropriately selected depending on the display device to which it is applied, and is preferably 0.1 to 5 μm, and more preferably 0.2 to 3 μm.
[0178] In one embodiment of the present invention, the optical film of the present invention preferably has a dichroic ratio of 20 or more. Here, the so-called dichroic ratio is the absorption intensity ratio of two linear polarizations of light incident on the light absorption anisotropic film and vibrating perpendicularly to each other, and refers to the ratio (A2 / A1) of the absorbance A1(λ) in the orientation direction relative to the light of wavelength λnm and the absorbance A2(λ) in the perpendicular direction within the orientation plane. In the present invention, an optical film with a dichroic ratio of 20 or more can be obtained by aligning the polymerizable compound (1) and the dichroic dye in the horizontal direction relative to the plane of the light absorption anisotropic film. The higher the dichroic ratio, the more excellent the absorption selectivity of the polarizing film. In the optical film of the present invention, the dichroic ratio is more preferably 30 or more. It should be noted that, although it also depends on the type of dichroic dye, in the case of a liquid crystal cured film cured in a nematic liquid crystal phase, the dichroic ratio is about 5 to 10.
[0179] The dichroic ratio can be measured, for example, by the method described in Examples below.
[0180] The optical film of the present invention has excellent polarization performance, so it can be suitable for various display devices. The so-called display device is a device having a display mechanism, including a light-emitting element or a light-emitting device as a light source. As a display device, for example, a liquid crystal display device, an organic electroluminescent (EL) display device, an inorganic electroluminescent (EL) display device, a touch panel display device, an electron emission display device (field emission display device (FED, etc.), a surface field emission display device (SED)), an electronic paper (a display device using electronic ink, an electrophoretic element), a plasma display device, a projection display device (a grating light valve (GLV) display device, a display device with a digital micromirror device (DMD), etc.) and a piezoelectric ceramic display, etc., are particularly preferred, and an organic EL display device and a touch panel display device are particularly preferred, and an organic EL display device is particularly preferred. For example, an optical film comprising a light absorption anisotropic film formed by a polymerizable composition comprising a polymerizable compound (1) of the present invention is attached to the surface of a display device via an adhesive or an adhesive, so that a display device comprising the optical film of the present invention can be obtained.
[0181] Example
[0182] Hereinafter, the present invention will be described in further detail by way of Examples. "%" and "parts" in the examples are by mass % and by mass parts unless otherwise specified.
[0183] The HPLC measurement for analyzing each compound may be performed under any conditions as long as the peak derived from each polymerizable compound can be separated. An example of the HPLC measurement conditions is shown below.
[0184] (Measurement conditions)
[0185] Measurement apparatus: HPLC LC-10AT (manufactured by Shimadzu Corporation)
[0186] Chromatographic column: L-Column ODS (inner diameter 3.0mm, length 150mm, particle size 3μm)
[0187] Temperature: 40℃
[0188] Mobile phase A: 0.1% (v / v)-TFA / water
[0189] Mobile phase B: 0.1% (v / v)-TFA / acetonitrile
[0190] Gradient: 0min 70%-B
[0191] 30min 100%-B
[0192] 60min 100%-B
[0193] 60.01min 70%-B
[0194] 75min 70%-B
[0195] Flow rate: 0.5mL / min
[0196] Injection volume: 5μL
[0197] Detection wavelength: 254nm
[0198] 1. Synthesis of Compound (A-1) and Compounds (C-1) to (C-5)
[0199] Compound (A-1) and compounds (C-1) to (C-5) were prepared by the following method.
[0200] (1) Synthesis of Compound (A-1)
[0201] The compound (A-1) having the following structure was synthesized by the method described in Liquid Crystals, 1995, Vol. 18, No. 2, 319-326.
[0202] [Chemical formula 15]
[0203]
[0204] (2) Synthesis of Compound (C-1)
[0205] The compound (C-1) having the following structure was synthesized according to the following route.
[0206] [Chemical formula 16]
[0207]
[0208] (i) Synthesis of Compound (B-1)
[0209] A 100 mL four-necked flask equipped with a serpentine condenser and a thermometer was set to a nitrogen atmosphere, and 10.3 g of trans-1,4-cyclohexanedicarboxylic acid, 15.0 g of compound (D-1) (manufactured by Tokyo Chemical Industry Co., Ltd.), and K 2 CO 3 After mixing 16.5 g of methyl pyrrolidone (manufactured by FUJIFILM WakoPure Chemical Corporation) and 150 g of N-methyl-2-pyrrolidone (manufactured by Kanto Chemical Co., Ltd.), the mixture was heated to 100° C. and reacted for 3 hours. After cooling, the reaction mass was added to 750 g of water, concentrated hydrochloric acid was added until the pH was less than 4, and then 800 g of ethyl acetate was added to recover the organic layer.
[0210] The organic layer was further washed twice with 500 g of water, and the solvent was distilled off by concentration. The obtained crude product was dissolved in toluene, the insoluble components were removed by filtration, and then toluene was removed by concentration distillation to obtain 12.7 g of compound (B-1). Based on compound (D-1), the yield of compound (B-1) was 62.1%.
[0211] (ii) Synthesis of Compound (C-1)
[0212] A 100 mL four-necked flask equipped with a serpentine condenser and a thermometer was placed in a nitrogen atmosphere, and 10.0 g of compound (B-1), 40.0 g of N,N-dimethylacetamide (manufactured by Kanto Chemical Co., Ltd.), 5.4 g of N,N-dimethylaniline (manufactured by Kanto Chemical Co., Ltd.), and 0.3 g of BHT (butylated hydroxytoluene, manufactured by FUJIFILM Wako Pure Chemical Corporation) were added and mixed, and then cooled to 0°C, and 3.2 g of acryloyl chloride (manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise over 1 hour, and the mixture was reacted for 5 hours. After the reaction was completed, concentrated hydrochloric acid was added to adjust the pH to less than 4, 80 g of ethyl acetate was added, and then 120 g of water was added to recover the organic layer. The mixture was further separated with 120 g of water, and ethyl acetate was distilled off from the organic layer by concentration. The crude product obtained was purified by silica gel chromatography to obtain 5.5 g of compound (C-1).
[0213] The yield of compound (C-1) was 47.4% based on compound (B-1).
[0214] (3) Synthesis of Compound (C-4)
[0215] Compound (C-4) having the following structure was synthesized by the same procedure as in the synthesis of compound (C-1), except that compound (D-4) was used instead of compound (D-1).
[0216] [Chemical formula 17]
[0217]
[0218] (4) Synthesis of Compound (C-5)
[0219] Compound (C-5) having the following structure was synthesized by the same procedure as in the synthesis of compound (C-1), except that compound (D-5) was used instead of compound (D-1).
[0220] [Chemical formula 18]
[0221]
[0222] (5) Synthesis of Compound (C-2)
[0223] The compound (C-2) having the following structure was synthesized according to the following route.
[0224] [Chemical formula 19]
[0225]
[0226] A 100 mL four-necked flask equipped with a serpentine condenser and a thermometer was set to a nitrogen atmosphere, and 47.8 g of trans-1,4-cyclohexanedicarboxylic acid, 20.0 g of compound (D-2) (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.18 g of DMAP (N,N-dimethylaminopyridine, manufactured by FUJIFILM Wako Pure Chemical Corporation), 0.44 g of BHT (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 95 g of N-methyl-2-pyrrolidone (manufactured by Kanto Chemical Co., Ltd.) were added and mixed, and 22.8 g of IPC (diisopropylcarbodiimide, manufactured by FUJIFILM Wako Pure Chemical Corporation) was further added using a dropping funnel, and these were reacted overnight at 40° C. After the reaction was completed, the insoluble components were removed by silica gel filtration, 200 g of ethyl acetate was added to the filtrate, and washed with 500 g of water. The obtained ethyl acetate solution was concentrated and distilled to remove the solvent, and the obtained crude product was purified by silica gel chromatography to obtain 23.4 g of compound (C-2). The yield of compound (C-2) was 53.2% based on compound (D-2).
[0227] (6) Synthesis of Compound (C-3)
[0228] A compound (D-3) having the following structure was synthesized by the same procedure as in the synthesis of the compound (C-2), except that 11-bromodecanecanoic acid was used instead of trans-1,4-cyclohexanedicarboxylic acid.
[0229] [Chemical formula 20]
[0230]
[0231] Compound (C-3) was synthesized by the same procedure as in the synthesis of compound (B-1), except that compound (D-3) was used instead of compound (D-4).
[0232] [Chemical formula 21]
[0233]
[0234] 2. Synthesis of polymerizable compounds
[0235] (1) Synthesis Example 1 (Example)
[0236] The compound (1-a) having the following structure was synthesized according to the following route.
[0237] [Chemical formula 22]
[0238]
[0239] A 100 mL four-necked flask equipped with a serpentine condenser and a thermometer was placed in a nitrogen atmosphere, and 3.1 g of compound (A-1), 3.0 g of compound (C-1), 0.02 g of DMAP (manufactured by FUJIFILM Wako Pure Chemical Corporation), 0.1 g of BHT (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 23.0 g of chloroform (manufactured by Kanto Chemical Co., Ltd.) were added and mixed, and 1.0 g of IPC (manufactured by FUJIFILM Wako Pure Chemical Corporation) was further added using a dropping funnel, and they were reacted at 0°C overnight. After the reaction was completed, the insoluble components were removed by silica gel filtration. The obtained chloroform solution was concentrated and distilled to remove the solvent, and the obtained crude product was purified by silica gel chromatography to obtain 5.2 g of polymerizable compound (1-a). Based on compound (A-1), the yield of polymerizable compound (1-a) was 90.8%.
[0240] (2) Synthesis Example 2 (Example)
[0241] A polymerizable compound (1-b) was synthesized in the same manner as in Synthesis Example 1 except that the compound (C-2) was used instead of the compound (C-1).
[0242] (3) Synthesis Example 3 (Example)
[0243] A polymerizable compound (1-c) was synthesized in the same manner as in Synthesis Example 1 except that the compound (C-3) was used instead of the compound (C-1).
[0244] (4) Synthesis Example 4 (Example)
[0245] A polymerizable compound (1-d) was synthesized in the same manner as in Synthesis Example 1 except that the compound (C-4) was used instead of the compound (C-1).
[0246] (5) Synthesis Example 5 (Example)
[0247] A polymerizable compound (1-e) was synthesized in the same manner as in Synthesis Example 1 except that the compound (C-5) was used instead of the compound (C-1).
[0248] (6) Synthesis Example 6 (Comparative Example)
[0249] A polymerizable compound (1-f) having the following structure was synthesized by the method described in Lub et al. Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996).
[0250] [Chemical formula 23]
[0251]
[0252] 3. Evaluation of polymerizable compounds
[0253] (1) Determination of phase transition temperature
[0254] (i) Production of laminated body
[0255] 〔Preparation of oriented film〕
[0256] A 2 mass % aqueous solution of polyvinyl alcohol (polyvinyl alcohol 1000 fully saponified type, manufactured by Wako Pure Chemical Industries, Ltd.) was applied to a glass substrate by spin coating, and after drying, a film with a thickness of 100 nm was formed. Next, the surface of the obtained film was subjected to a rubbing treatment, thereby forming an oriented film. For the rubbing treatment, a semi-automatic rubbing device (trade name: LQ-008, manufactured by Choyo Engineering Co., Ltd.) was used, using a cloth (trade name: YA-20-RW, manufactured by Yoshikawa Chemical Industry Co., Ltd.), and the process was carried out under the conditions of a thrust amount of 0.15 mm, a rotation speed of 500 rpm, and a speed of 16.7 mm / s. Through the above-mentioned rubbing treatment, a laminate 1 having an oriented film formed on a glass substrate was obtained.
[0257] (ii) Determination of phase transition temperature
[0258] 1.00 g of each of the polymerizable compounds (1-a) to (1-f) prepared in Synthesis Examples 1 to 6 was measured in a vial, and 2.00 g of chloroform was further added to dissolve the polymerizable compounds. The obtained solution was applied to the laminate 1 and dried. The obtained laminate was placed in a cooling and heating device ("LNP94-2" manufactured by Japan High Tech Co., Ltd.), and the temperature was raised from room temperature to 120°C, and then cooled to room temperature. A polarizing microscope (LEXT, manufactured by Olympus Corporation) was used to observe the changes during cooling and determine the temperature at which the phase transition occurs. The results are shown in Table 1.
[0259] It should be noted that, in Table 1, "I" refers to a liquid phase, "N" refers to a nematic liquid crystal phase, "SmA" refers to a smectic A liquid crystal phase, and "SmB" refers to a smectic B liquid crystal phase. For example, Synthesis Example 1 shows that the liquid phase is transformed into a nematic liquid crystal phase at 93°C, the nematic liquid crystal phase is transformed into a smectic A liquid crystal phase at 92°C, and the smectic A liquid crystal phase is transformed into a smectic B liquid crystal phase at 70°C.
[0260] (2) Solubility evaluation
[0261] 1.00 g of o-xylene and a stirrer were placed in a vial at 25°C, and the polymerizable compounds (1-a) to (1-f) prepared in Synthesis Examples 1 to 6 were added while stirring with a magnetic stirrer (HS-30DN, ASONE CORPORATION) until a dissolved residue was visually observed. When a dissolved residue was observed, the solubility of each compound in o-xylene was calculated as a weight percentage concentration from (weight of each compound) / (weight of each compound + weight of o-xylene). The results are shown in Table 1.
[0262] [Table 1]
[0263]
[0264] 4. Preparation of polymerizable composition
[0265] (1) Embodiment 1
[0266] (i) Preparation of polymerizable composition
[0267] The following components were mixed and stirred at 80° C. for 1 hour to obtain a polymerizable composition 1. As the dichroic dye, an azo dye described in Examples of JP-A-2013-101328 was used.
[0268] · 100 parts of polymerizable compound (1-a)
[0269] [Chemical formula 24]
[0270]
[0271] · 2.8 parts of the dichroic dye (1) shown below
[0272] [Chemical formula 25]
[0273]
[0274] · 2.8 parts of the dichroic dye (2) shown below
[0275] [Chemical formula 26]
[0276]
[0277] · 2.8 parts of the dichroic dye (3) shown below
[0278] [Chemical formula 27]
[0279]
[0280] Polymerization initiator:
[0281] 2-Dimethylamino-2-benzyl-1-(4-morpholinophenyl)-1-butanone (Irgacure 369; manufactured by Ciba Specialty Chemicals) 6 parts
[0282] Leveling agent:
[0283] Polyacrylate compound (BYK-361N; manufactured by BYK-Chemie) 1.2 parts
[0284] Solvent: 250 parts of o-xylene
[0285] (ii) Determination of phase transition temperature
[0286] The polymerizable composition 1 was applied to a glass substrate with a PVA orientation film and subjected to a rubbing treatment, obtained in the same manner as the laminate 1 used for measuring the phase transition temperature of the polymerizable compounds (1-a) to (1-f), and the temperature was raised from room temperature to 150° C. and then cooled to room temperature. The change during cooling was observed with a polarizing microscope, and the temperature at which the phase transition occurred was measured. The results are shown in Table 2.
[0287] It should be noted that the symbols indicating phase transition in Table 2 have the same meanings as those in Table 1.
[0288] (2) Embodiment 2
[0289] A polymerizable composition 2 was prepared in the same manner as in Example 1 except that the polymerizable compound (1-b) was used instead of the polymerizable compound (1-a). The phase transition temperature of the obtained polymerizable composition was measured in the same manner as in Example 1. The results are shown in Table 2.
[0290] (3) Embodiment 3
[0291] The same procedure as in Example 1 was carried out except that the polymerizable compound (1-c) was used instead of the polymerizable compound (1-a) to prepare a polymerizable composition 3. The phase transition temperature of the obtained polymerizable composition was measured in the same manner as in Example 1. The results are shown in Table 2.
[0292] (4) Embodiment 4
[0293] A polymerizable composition 4 was prepared in the same manner as in Example 1 except that the polymerizable compound (1-d) was used instead of the polymerizable compound (1-a). The phase transition temperature of the obtained polymerizable composition was measured in the same manner as in Example 1. The results are shown in Table 2.
[0294] (5) Embodiment 5
[0295] The same procedure as in Example 1 was carried out except that the polymerizable compound (1-e) was used instead of the polymerizable compound (1-a) to prepare a polymerizable composition 5. The phase transition temperature of the obtained polymerizable composition was measured in the same manner as in Example 1. The results are shown in Table 2.
[0296] (6) Comparative Example 1
[0297] A polymerizable composition 6 was prepared in the same manner as in Example 1 except that the polymerizable compound (1-f) was used instead of the polymerizable compound (1-a). The phase transition temperature of the obtained polymerizable composition was measured in the same manner as in Example 1. The results are shown in Table 2.
[0298] 5. Determination of dichroic ratio
[0299] (1) Formation of polarizing film
[0300] The polymerizable composition 1 was applied on the oriented film of the laminate 1 by spin coating, and after heating and drying on a hot plate at 120° C. for 1 minute, it was rapidly cooled to room temperature to form a dry film containing the oriented polymerizable compound (1-a) on the oriented film. Next, a UV irradiation device (SPOT CURE SP-7; manufactured by Ushio Inc.) was used at an exposure dose of 2000 mJ / cm 2 The dried film is irradiated with ultraviolet rays (365 nm standard), thereby polymerizing the polymerizable compound (1-a) contained in the dried film while maintaining the oriented state, and forming a polarizing film (1) from the dried film.
[0301] (2) Determination of dichroic ratio
[0302] A holder (folder) having the polarizing film (1) produced in the above manner was placed in a spectrophotometer (UV-3150 manufactured by Shimadzu Corporation) and the absorbance (A1) in the transmission axis direction and the absorbance (A2) in the absorption axis direction at 550 nm were measured by a double beam method. A mesh that intercepts 50% of the light was placed on the reference side of the holder. The ratio (A2 / A1) was calculated from the measured values of the absorbance (A1) in the transmission axis direction and the absorbance (A2) in the absorption axis direction as the dichroic ratio.
[0303] It should be noted that the so-called transmission axis refers to the polarization direction of the component of the incident light that passes through the polarizing film, and the so-called absorption axis refers to the polarization direction of the component of the incident light that is absorbed by the polarizing film.
[0304] The dichroic ratio was evaluated according to the following evaluation criteria. The results are shown in Table 2.
[0305] A: More than 30
[0306] B: 20 or more to less than 30
[0307] C: 10 or more to less than 20
[0308] D: 0 or more to less than 10
[0309] [Table 2]
[0310]
[0311] By using the polymerizable compound of the present invention, the phase transition temperature is lowered, and film formation under lower temperature conditions can be achieved.
Claims
1. A polymerizable compound represented by the following formula (1), [Chemical formula 28] In formula (1), X1 and X2 are each independently a 1,4-phenylene group which may have a substituent or a cyclohexane-1,4-diyl group which may have a substituent (wherein, At least one of X1 and X2 is 1,4-phenylene which may have a substituent, -CH2- constituting the cyclohexane-1,4-diyl group may be replaced by -O-, -S- or -NR-, and R represents an alkyl group having 1 to 6 carbon atoms or a phenyl group, Y1 represents -CH2CH2-, -CH2O-, -COO-, -OCO-, -OCOO-, a single bond, -N=N-, -CR a =CR b -, -C≡C- or -CR a =N-,R a and R b each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, U1 and U2 independently represent a hydrogen atom or a polymerizable group (wherein, At least one of U1 and U2 is a polymerizable group), W1 represents a single bond, -O-, -S-, -COO-, -OCO- or -OCOO-, V1 and V2 independently represent an alkanediyl group having 1 to 20 carbon atoms which may have a substituent, and -CH2- constituting the alkanediyl group may be replaced by -O-, -S-, -NH-, -COO-, -OCO- or -OCOO-. 2 . The polymerizable compound according to claim 1 , which exhibits a smectic liquid crystal phase.
3. The polymerizable compound according to claim 1, wherein In the formula (1), Y1 is a divalent group represented by -COO- or -OCO-, and W1 is a divalent group represented by -O-, -COO- or -OCO-.
4. The polymerizable compound according to claim 1, wherein U1 and U2 in formula (1) are acryloyloxy groups. 5 . A polymerizable composition comprising a dichroic pigment and the polymerizable compound according to claim 1 . The polymerizable composition according to claim 5 , further comprising a solvent. 7 . An optical film comprising a polymer of the polymerizable compound according to claim 1 or a cured product of the polymerizable composition according to claim 5 . The optical film according to claim 7 , which has a dichroic ratio of 20 or more.
9. A display device comprising the optical film according to claim 8.
